Community Based Tourism as a Strategy for Empowerment and Community Welfare Improvement in Bandar Kidul Weaving Village, Kediri - Aprilla Intan Fatima; Susi Hardjati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the application of Community Based Tourism in the development of the Bandar Kidul Ikat Weaving Tourism Village, Kediri City. The method used is descriptive with a qualitative approach. Research informants include the Sub-Coordinator of Tourism Object Development of the Kediri City Culture, Tourism, Youth, and Sports Office, Tourism Awareness Group, weaving and culinary MSMEs, craftsmen, and visitors. Data were collected through observation, interviews, and documentation, then analyzed using the stages of data collection, data condensation, data display, and conclusion drawing/verification. Based on the research results, the application of the Community Based Tourism (CBT) principle in the Bandar Kidul Ikat Weaving Tourism Village, Kediri City, as stated by Harold Goodwin and Santilli (2009), has been successfully implemented and has had a positive impact on improving community welfare, as follows: 1) Social Capital and Empowerment: Participation, Active community participation in various tourism activities has strengthened cultural identity and provided tangible economic benefits; 2) Local Economic Development, a community-based tourism ecosystem has created jobs and encouraged the growth of local businesses that increase residents' income; 3) Commercial Viability: Sustainability, the preservation of weaving culture accompanied by innovation and the involvement of the younger generation ensures sustainability and becomes a source of community welfare; and 4) Collective Benefits: Capacity Building, ongoing training increases community capacity in managing tourism and opens up new economic opportunities through increased tourist visits.